2019
DOI: 10.1051/0004-6361/201935633
|View full text |Cite
|
Sign up to set email alerts
|

Substructures in the Keplerian disc around the O-type (proto-)star G17.64+0.16

Abstract: We present the highest angular resolution (∼20 × 15 mas–44 × 33 au) Atacama Large Millimeter/sub-millimeter Array (ALMA) observations that are currently possible of the proto-O-star G17.64+0.16 in Band 6. The Cycle 5 observations with baselines out to 16 km probe scales < 50 au and reveal the rotating disc around G17.64+0.16, a massive forming O-type star. The disc has a ring-like enhancement in the dust emission that is especially visible as arc structures to the north and south. The Keplerian kinematics a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 67 publications
(65 reference statements)
2
39
0
Order By: Relevance
“…In massive protostellar sources, earlier results showed that most Keplerian disk candidates are stable with Q > 1 ( Beltrán and de Wit 2016), in which the temperature of the disk are probed by observations of rotational lines of species such as CH 3 CN and CH 3 OH, and the surface density is estimated from the dust continuum emission. The more recent studies for G351.77−0.54 and G17.64+0.16 are consistent with this scenario, both having disks that appear stable against collapse and fragmentation (Beuther et al 2017;Maud et al 2019). The Q parameter for G17.64+0.16 reaches its lowest values of 2-4 towards the ring-like structure seen in dust emission.…”
Section: Gravitational Instabilities and Binary Formation In High Massupporting
confidence: 61%
“…In massive protostellar sources, earlier results showed that most Keplerian disk candidates are stable with Q > 1 ( Beltrán and de Wit 2016), in which the temperature of the disk are probed by observations of rotational lines of species such as CH 3 CN and CH 3 OH, and the surface density is estimated from the dust continuum emission. The more recent studies for G351.77−0.54 and G17.64+0.16 are consistent with this scenario, both having disks that appear stable against collapse and fragmentation (Beuther et al 2017;Maud et al 2019). The Q parameter for G17.64+0.16 reaches its lowest values of 2-4 towards the ring-like structure seen in dust emission.…”
Section: Gravitational Instabilities and Binary Formation In High Massupporting
confidence: 61%
“…To identify the subset of PV models that provide a reasonable representation of our data, we employ a by-eye approach similar to that of Maud et al (2018Maud et al ( , 2019 and Ilee et al (2018). As our primary aim is to constrain the enclosed (and so the stellar) mass, we fix R out to 2000 AU based on the extent of the 1.05 mm dust continuum emission (≈ 0.5× the geometric mean of the major and minor axes from Table 2), which is in reasonable agreement with the extent of the compact molecular line emission (Figure 3).…”
Section: Kinematic Modelling Of Mm1mentioning
confidence: 99%
“…An enclosed stellar mass of ∼33−65 M corresponding to a single MYSO would place G19.01−0.03 MM1 among the most massive proto-O star candidates discovered to date. Of the handful of sources with reported central stellar masses >30 M (AFGL 2591-VLA3, G11.92−0.61 MM1, G17.64+0.16, G31.41+0.31: Jiménez-Serra et al 2012;Ilee et al 2018;Maud et al 2019;Beltrán et al 2018, respectively; see also Johnston et al 2020), only G17.64+0.16 (AFGL 2136) and AFGL 2591-VLA3 have central stellar masses ≥40 M and both have luminosities ≥10 5 L . Theoretical models of accreting protostars also predict L>10 5 L for M * >30 M (e.g.…”
Section: The Nature Of Mm1mentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 2, 3, and 4 show how the QA2 images are typically limited to only a portion of the data while ARI-L images provide a more complete overview of the data content. In figure 2, we show that the QA2 package includes images for 2 of the 13 spectral windows observed for an O-type young stellar object (G345.49+1.47) to study kinematic structures in dense, warm gas associated with star formation (Cesaroni et al 2017, Moscadelli et al 2019, Maud et al 2019. The complete spectral coverage of the ARI-L cubes (see Fig.…”
Section: Examples Of Ari-l Productsmentioning
confidence: 99%